Intracranial Atypical Teratoid/Rhabdoid Tumor during Infancy: A Case Report - Bita Geramizadeh; Mohammad Reza Farzaneh; Ahmad Kamgarpour (Middle East Journal of Cancer, 2016)
Central nervous system atypical teratoid/rhabdoid tumor during infancy is a rare, highly aggressive tumor most commonly seen in the cerebellar area. Herein we describe the case of a 4-month-old baby who presented with convulsions. Pathologic examination of her cerebellar mass showed an atypical teratoid/rhabdoid tumor. The patient died 5 days after surgery despite complete excision of the mass and prior to chemoradiation. Histopathologic diagnosis of this tumor type should be considered in posterior fossa masses of children, particularly before the age of 2 years, because the treatment protocol and prognosis of this tumor completely differ from other tumors of this region such as medulloblastoma and primitive neuroectodermal tumors.